First partner event of the CGIAR Antimicrobial Resistance Hub: Jonathan Wadsworth - Wadsworth, Jonathan (International Livestock Research Institute, 2019)
The World Bank Group's Jonathan Wadsworth talks about the importance of the CGIAR Antimicrobial Resistance (AMR) Hub, which was launched 21 February 2019 at ILRI in Nairobi, Kenya. Scientists working at this ILRI-hosted hub aim to help reduce agriculture-associated antimicrobial resistance in low- and middle-income countries. Working in a wealth of partnerships with national governments and agencies, the hub will apply one-health approaches to managing agriculture-associated antimicrobial risks.